Long-Term Interactions of Salmonella Enteritidis With a Lytic Phage for 21 Days in High Nutrients Media - Barron-Montenegro, Rocio; Rivera, Dácil; Serrano, María Jesus; García, Rodrigo; Álvarez, Diana M.; Benavides, Julio; Arredondo, Fernanda; Álvarez, Francisca P.; Bastías, Roberto; Ruiz, Soledad; Hamilton-West, Christopher; Castro-Nallar, Eduardo; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Salmonella spp. is a relevant foodborne pathogen with worldwide distribution. To mitigate Salmonella infections, bacteriophages represent an alternative to antimicrobials and chemicals in food animals and food in general. Bacteriophages (phages) are viruses that infect bacteria, which interact constantly with their host. Importantly, the study of these interactions is crucial for the use of phages as a mitigation strategy. In this study, experimental coevolution of Salmonella Enteritidis (S. Enteritidis) and a lytic phage was conducted in tryptic soy broth for 21 days. Transfer to fresh media was conducted daily and every 24 hours, 2 mL of the sample was collected to quantify Salmonella OD600 and phage titter. Additionally, time-shift experiments were conducted on 20 colonies selected on days 1, 12, and 21 to evaluate the evolution of resistance to past (day 1), present (day 12), and future (day 21) phage populations. The behavior of the dynamics was modeled and simulated with mathematical mass-action models. Bacteria and phage from days 1 and 21 were sequenced to determine the emergence of mutations. We found that S. Enteritidis grew for 21 days in the presence and absence of the phage and developed resistance to the phage from day 1. Also, the phage was also able to survive in the media for 21 days, however, the phage titer decreased in approx. 3 logs PFU/mL. The stability of the lytic phage population was consistent with the leaky resistance model. The time-shift experiments showed resistance to phages from day 1 of at least 85% to the past, present, and future phages. Sequencing of S. Enteritidis showed mutations in genes involved in lipopolysaccharide biosynthesis genes rfbP and rfbN at day 21. The phage showed mutations in the tail phage proteins responsible for recognizing the cell surface receptors. These results suggest that interactions between bacteria and phage in a rich resource media generate a rapid resistance to the infective phage but a fraction of the population remains susceptible. Interactions between Salmonella and lytic phages are an important component for the rational use of phages to control this important foodborne pathogen.